Tonsillitis and Peritonsillar Abscess: What Does the Practitioner Need to Know - A.V. Savustyanenko (Zaslavsky O.Yu., 2013)
More often the cause of bacterial tonsillitis are group A β-haemolytic streptococci. Infection can also be spread on the pharynx (pharyngo-tonsillitis) and manifests by acute pain, severe pain on swallowing, fever (> 38 °C), enlarged tonsils, tonsillopharyngeal erythema, palpatory tenderness of enlarged anterior cervical lymph nodes (lymphadenitis). The disease is complicated by co-pathogenic strains of Haemophilus influenzae, Haemophilus parainfluenzae, Moraxella catarrhalis, Staphylococcus aureus which produce β-lactamase that increase the resistance to penicillin treatment. Diagnosis as usual is based on the clinical manifestation of disease. The goals of therapy include the treatment of tonsillitis and its complications as well as prevention of transmission of infection to other people. AugmentinТМ is a first choice option to treat tonsillitis. This drug is a combination of amoxicillin (semisynthetic penicillin) and clavulanic acid (β-lactamase inhibitor) and possesses effect against group A β-haemolytic streptococci and co-pathogens, that enable the achievement of the aforementioned goals of the therapy. One of the complications of tonsillitis is peritonsillar abscess which need surgical treatment (aspiration of pus or making incision with drainage) and antibiotic therapy with Augmentin.